Subject Alternation and Antecedent Preference in Romanian - Fabian Istrate; Anne Abeillé; Barbara Hemforth (Discours)
In this paper, we will study the use of null pronouns on the one hand and the interpretation of null and pronominal subjects on the other hand in Romanian. While both questions have been studied across a wide range of Romance languages, empirical data on Romanian are still missing in the literature. Our first three experiments, using a binary choice of possible answers to questions, show that null subjects are generally preferred in Romanian. This preference is, however, modified by the contrast effect with more pronominal subjects when there is an alternative explicit or presupposed referent in the context. In our fourth experiment, we find that, as in other Romance languages, null subjects prefer a subject antecedent while pronominal subjects prefer a non-subject antecedent, showing the typical division of labour effect. The preference for null subjects in our experiment is slightly smaller than in Italian or European Portuguese, two languages that show a stronger division of labour effect with near categorical choices of subject and object antecedents for null and pronominal subjects, respectively. Preferences found for Romanian resemble those found for Spanish. We argue that the frequency of null subjects in a language may play a role in the strength of the division of labour effect.